Developing Critical and Creative Thinking Skills Through the Cooperative Learning Model of Team Games Tournament in Islamic Education at SMPN 1 Babat Lamongan - Muhammad Fajar Haqquddin; Rusman Rusman; Syahraini Tambak; Adi Wibowo (CV. Zamron Pressindo, 2024)
Research Objective– This study aims to develop students' critical and creative thinking skills through the implementation of the Team Games Tournament (TGT) cooperative learning model in Islamic Education (PAI) at SMPN 1 Babat Lamongan. Methodology– The research employs a qualitative approach with a descriptive method. Data were collected through observations, interviews, and field notes and analyzed interactively to identify the impact of the TGT model on students' critical and creative thinking skills. Findings– The findings indicate that implementing the TGT model significantly enhances students' abilities to analyze, evaluate, and generate new ideas. This model also motivates students to actively participate, collaborate within groups, and promote higher-order thinking. Moreover, TGT creates an enjoyable learning environment, increases student engagement, and aids in better understanding of the material. Research Implications/Limitations– The study highlights the importance of applying cooperative learning models like TGT to support the development of 21st-century skills, including critical and creative thinking, particularly in Islamic Education. However, this study is limited to the context of a specific school and requires further research for broader generalization. Originality/Value– This research provides an original contribution by integrating the TGT learning model into Islamic education to develop students' critical and creative thinking skills. This approach is relevant for preparing students to face complex challenges in the modern era.